Metabolomics: Recent Advances and Future Prospects Unveiled - Sharma, Shweta; Singh, Garima; Akhter, Mymoona (Current Bioinformatics, 2024)
In the era of genomics, fueled by advanced technologies and analytical tools, metabolomics has become a vital component in biomedical research. Its significance spans various domains, encompassing biomarker identification, uncovering underlying mechanisms and pathways, as well as the exploration of new drug targets and precision medicine. This article presents a comprehensive overview of the latest developments in metabolomics techniques, emphasizing their wide-ranging applications across diverse research fields and underscoring their immense potential for future advancements.
Keywords: forensic science